Shortening of the Slavic long circumflex - one mora law in Croatian - Kapović, Mate (Array, 2011)
The article deals with the precise rules for the shortening of the Proto-Slavic old long circumflex in Croatian. The conditions of the shortening are explained in mora terms and a special emphasis is put on the evidence coming from -an and -ak adjectives.